Morbidity profile of adolescents reported to an urban health center in Kancheepuram district of Tamil Nadu, India - Sivagurunathan, Chinnaian; Gopalakrishnan, Sekaran; Umadevi, Ramachandran; Kumar, Pandurangan Mohan (International Journal Of Community Medicine And Public Health, 2017)
Background:Adolescents are the group of children transforming to adults (aged 10 to 19 years). There are more than 1.2 billion adolescents worldwide and about 243 million live in India i.e. about 20% of Indian population. They are apparently healthy people but they do also have health related issues. Objective of this study was to determine the morbidity pattern prevalent among adolescents who attended an urban health training centre in Kancheepuram district. Methods:A cross sectional study was carried among 918 adolescents aged between 10 to 19 years, who visited the urban health training centre during the study period using convenient sampling technique. Data collection was done by using a structured questionnaire which consisted of questions related to their demographic characteristics and the reason for coming to the centre seeking medical help. Data analysis was done using SPSS version 16 and the results expressed in percentages. Results:Among the study population of 918, 57% were males and 43% were females. About 81.8% were studying while 17.7% were working. About 78.2% adolescents (84.3% of males and 70.1% females), were suffering from acute conditions while 21.8% (15.7 % males and 29.9% females) were suffering from chronic conditions. Among the acute conditions, upper respiratory tract infection constituted 22.5% of complaints followed by musculo-skeletal, gastrointestinal and ENT problems. The most common chronic condition reported was anemia (6.2%) which was followed by acne on their face and minor psychiatric illnesses like anxiety and depression. Conclusions:Improvement in the quality of diagnosis and treatment for both acute and chronic illnesses among adolescents are required to be implemented at all levels.